Influence of seasons and land-use practices on soil microbial activity and metabolic diversity in the “Montado ecosystem” - Costa, Dalila; Freitas, Helena; Sousa, José Paulo (European Journal of Soil Biology, 2013)
The “Montado ecosystem” is important both economically and ecologically; this ecosystem is dominated by cork and holm oak trees (Quercus suber L. and Quercus rotundifolia Lam. respectively) combined with a rotation of crops/fallow/pastures. Diverse management strategies, deviating from the sustainable use of the ecosystem, have been implemented, from which arise some extreme situations of over-use or abandonment. To evaluate the effects of different soil use and management, namely extensive cropping, intensive pasture and abandonment, in the activity of soil microorganisms, dehydrogenase, acid phos- phatase, b-glucosidase and urease activities, N-mineralization and nitrification rates were measured in different land-use practices, in different seasons (winter, spring and autumn). Also, the potential metabolic diversitywas evaluated by analysis of community-level physiological profiles (CLPPs). Seasonal effects were evident with maximum activity occurring in rainy seasons (winter and autumn) and lower substrate utilization in winter. Significant correlations between most microbial parameters and soil water content reflect this seasonal effect. Although showing mainly a seasonal change, microbial parameters were able to distinguish the abandoned area, with a general low activity and differential exponential rates in the use of several substrates, such as amino acids, miscellaneous and polymers, probably associated with changes in organic matter quality.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: Biolog; Land-use; Montado ecosystem; N-Mineralization; Nitrification; Soil enzymes

Soil organic matter quality and microbial catabolic functions along a gradient of wildfire history in a Mediterranean ecosystem - Guénon, René; Vennetier, Michel; Dupuy, Nathalie; Ziarelli, Fabio; Gros, Raphaël (Applied Soil Ecology, 2011)
The principal aim of this research was to determine the inﬂuence of an increasing wildﬁre history on the recovery at short and long term of soil organic matter (SOM) composition and microbial properties. The contemporary wildﬁre events (since 1950) were recorded for 27 plots located on the siliceous part of the French Mediterranean region (Maures mountain ranges). A wildﬁre history index was built, tested and calculated in order to display numerical values representative of the different wildﬁre history parameters (i.e. number of ﬁres, time since ﬁre and mean ﬁre interval). Microbial basal respiration and biomass were analysed as well as intensity of the use of 31 C-substrates, catabolic diversity and C-substrates utilisation proﬁles. Furthermore, a qualitative characterisation of the SOM was carried out by solid state 13 C NMR. Potential drivers of the microbial recovery were identiﬁed by studying the relationships between microbial activities and chemical functions of SOM. Our results showed that ﬁre histories resulting in considerable losses or alterations of SOM, such as recent or close ﬁres, decreased the microbial catabolic evenness. This could be attributed to a preferential utilisation of N-containing compounds and complex substrates such as aromatic and polymers reﬂecting a greater N microbial demand and a selection of speciﬁc catabolic functions. Moreover, a large number of ﬁres (4 ﬁres in 57 years compared to 1–2) resulted in lasting degradation of the relative intensity of methyl C function in polymethylene, O-Alkyl C, aromatic C and phenolic C functions inducing a slow-down in recovery of microbial properties. These results also conﬁrm our hypothesis that some chemical functions of SOM can be in equilibrium with wildﬁre history. Finally, this research demonstrates that FT-NIR analysis can be used as a valuable tool to assess both the wildﬁre history and the vulnerability of soil quality to shifts in historical ﬁre regimes
Keywords: 13C NMR; Biolog; Catabolic evenness; Fire recurrence; FT-NIR spectroscopy; Recovery